Aplicação do método Particle-in-Cell para cálculo de campos elétricos associados a linhas de transmissão em corrente alternada e contínua - Oliveira, Felipe Teodoro de (2018)
The inclusion of ultra-high voltage transmission lines in Brazilian power system brings the necessity of special consideration to corona effect, due to high potential gradients, and it demands larger right-of-ways (RoW). In this dissertation the numerical method Particle-in-Cell in its PPPM (particle-particle, particle-mesh) form is applied to the suggestion of a hybrid corridor with the Bipole ±800 kV CC Xingu - Terminal Rio and the TL 500 kV CA Fernão Dias - Terminal Rio, by the CoronaPIC software. Initially, the model behaviour is checked for AC transmission lines and its coherence for hybrid corridors application is verified by comparison with simulation results from other works. Subsequently, the electric field and current density profiles in the ground, together with ionic currents of the phases and poles, are evaluated and analysed with the inclusion of spacial charges influence for diverse wind conditions and distances between the lines. The method allows the consideration of mutual interactions between the lines that influence the superficial electric field of the cables and, ultimately, the charge generation.